The use of malacological analysis in studies on anthropogenic transformations in microhabitats: an example from the Cracow region, southern Poland - Alexandrowicz, Witold Pawel (ERDKUNDE, 2021)
The presented study is dedicated to the assessment of the scope and degree of anthropopressure, and the dependence of its intensity on the characteristics and nature of micro-environments. The research was based on the subfossil remains of molluscs. Eleven profiles of Late Holocene sediments in the Dulówka valley near Cracow were subjected to malacological analysis. In the upper part of the valley, there are calcareous tufas containing rich molluscan assemblages with a large share of shade-loving species. In the lower part, malacofauna dominated by open-country snails occurs in fluvial sediments. Radiocarbon dating has shown that mollusc-bearing deposits represent the last 2,000 years. The diversity of ecological features of molluscan assemblages in different parts of the valley depends on the intensity of anthropopressure. In the upper part, natural forest communities have survived to the present day, and anthropopressure has only been marked to a limited extent. The lower section has undergone a major transformation, mainly due to deforestation and the development of agricultural areas. Unfavorable terrain conditions for the human economy should be considered the major cause of the low anthropopressure intensity in the upper part of the valley. The malacological analysis used in the study allowed showing a significant diversity of microhabitats within the valley and its uneven susceptibility to human interference in natural processes.